Intrapartum cesarean delivery and the risk of perinatal complications in women with and without a single prior cesarean delivery. Issue 2 (14th July 2021) - Ashwal, Eran; Lavie, Anat; Blecher, Yair; Attali, Emmanuel; Aviram, Amir; Hadar, Eran; Lasry, Ariel; Yogev, Yariv; Hiersch, Liran
Abstract: Objective: To determine maternal and neonatal complications associated with an intrapartum cesarean delivery (CD) with and without a history of a previous CD. Methods: A retrospective cohort study of all women who underwent an unplanned intrapartum CD following a trial of labor in a university‐affiliated tertiary hospital, between 2009 and 2016. Perinatal outcomes of women with and without a history of a previous CD were compared. Composite adverse maternal outcome included one or more of the following: postpartum hemorrhage, need for blood transfusion, or cesarean hysterectomy. Composite adverse neonatal outcome included one or more of the following: 5‐min Apgar score <7, neonatal seizure, need for intubation, meconium‐aspiration‐syndrome, or hypoxic‐ischemic encephalopathy. Results: During the study period, 42 275 women attempted vaginal delivery. Of them, 2229 (5.3%) women underwent an unplanned intrapartum CD and met inclusion criteria: 337 (15.1%) with (study group) and 1892 (84.9%) without (control group) a previous CD. Women without a previous CD were younger and were characterized by higher rates of nulliparity and induction of labor compared with women with a previous CD. Other demographic and obstetrical characteristics did not differ between the groups. Indications for CD were also comparable between the groups. Uterine rupture complicated 2.3% of trials of labor among women with a previous CD. Adverse maternal (2.7% vs 2.9%, P  = 1.0) and neonatal (3.9% vs 4.3%, P  = 0.88) outcomes were comparable between the groups. After adjusting for potential confounders, a previous CD was not associated independently with adverse maternal outcomes (adjusted odds ratio [aOR] 0.86, 95% confidence interval [CI] 0.31–2.38; P  = 0.78) or neonatal outcomes (aOR 0.79, 95% CI 0.36–1.75; P  = 0.56). Conclusion: Our study provides evidence that perinatal outcomes of intrapartum CD delivery among women with a previous CD do not differ from those in women without a previous CD. These findings might improve the consultation and informed decision‐making process for couples considering a trial of labor after CD. Abstract : Perinatal outcomes of intrapartum cesarean delivery (CD) among women with a previous CD do not differ from those without a previous CD.